Treg-specific IL-27Rα deletion uncovers a key role for IL-27 in Treg function to control autoimmunity - Jeong‐su Do; Dongkyun Kim; Sohee Kim; Alice Valentin-Torres; Nina Dvorina; Eunjung Jang; Vivekananthan Nagarajavel; Tara M. DeSilva; Xiaoxia Li; Angela H. Ting; Dario A.A. Vignali; Stephen A. Stohlman; et al. (2017)
Significance Interleukin-27 (IL-27) can promote or antagonize inflammatory responses. However, the cellular mechanisms underlying such highly diverse roles remain unclear. It was proposed that IL-27 exerts antiinflammatory functions by directly acting on conventional CD4 T cells to induce IL-10–producing cells that are implicated in controlling inflammatory responses. Here, we have developed a Treg-specific IL-27Rα–deficient animal and observed that it is highly susceptible to autoimmune disease induction despite the presence of IL-10–producing T cells. We also show that systemic administration of IL-27 fails to attenuate ongoing inflammation in the absence of Treg expression of IL-27Rα. Therefore, IL-27 acting on Tregs plays a nonreplaceable role in controlling autoimmune inflammation, providing a rationale to develop a therapy by targeting IL-27 on Tregs.